Juvenile cystic adenomyosis: A case report and review of the literature. Issue 4 (3rd July 2019) - Deblaere, Lieselot; Froyman, Wouter; Van den Bosch, Thierry; Van Rompuy, Anne‐Sophie; Kaijser, Jeroen; Deprest, Jan; Timmerman, Dirk
Abstract: This report describes a case of a uterine cystic myometrial lesion in a 16‐year‐old adolescent girl presenting with pelvic pain and severe progressively worsening dysmenorrhoea. Patient's symptoms, ultrasound and MRI were suggestive of juvenile cystic adenomyosis (JCA). Medical treatment and alcohol sclerotherapy had a moderate and transient effect. The symptoms rapidly recurred, and the lesion was successfully excised via laparoscopic surgery. The treatment of JCA depends on patient's age, the symptoms' severity and the cyst location. Although rare, juvenile cystic adenomyosis should be considered in young women with severe dysmenorrhoea.